Analysis of the accuracy of reconstructed two teeth models manufactured using the 3DP and FDM technologies - Budzik, Grzegorz (Strojniški vestnik, 2016)
This paper presents results of the research focused on the accuracy of the manufacturing process of biomedical models, specifically tooth models. A patient's head was scanned with cone-beam computer tomography (CBCT). The best effect of tooth geometry reconstruction was obtained using the isotropic dimensions of voxel 0.2 mm x 0.2 mm x 0.2 mm. The same Hounsfield value was used (1254HU) and the method of segmentation (region growing) applied for the models of the teeth in the process of 3D reconstruction. The marching cubes algorithm, a method of surface rendering, allowed fully reconstructing the 3D geometry. The models were manufactured using two additive techniques (3DP and FDM). They were similarly aligned in the work space of both printers to maintain similar conditions of printing, and similar layer thicknesses of 0.1 mm and 0.13 mm were used. The printed models were scanned using a focus variation (FV) microscope. The scanned geometry of the models of the two teeth was compared with the geometry of the teeth after their segmentation and filtering. A fitting process was carried out using the best fit algorithm with a fitting condition of 0.001 mm. The achieved accuracy of the FV measurements was significantly higher than the accuracy of the used printing methods. FV can be applied to performing 3D scans of complex shapes such as the crown and roots of a tooth. 3DP models have more homogenous structure, whereas layer structure is easy to recognize for FDM models. Due to that, the 3DP models have to be strengthened using infiltration, which makes it more difficult to predict the final dimensions and to achieve required accuracy.
Keywords: dentalni modeli; hitra izdelava prototipov; spreminjanje gorišča; vzvratno inženirstvo